2014
DOI: 10.1016/j.socscimed.2013.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Labor migration, externalities and ethics: Theorizing the meso-level determinants of HIV vulnerability

Abstract: This paper discusses labor migration as an example of how focusing on the meso-level highlights the social processes through which structural factors produce HIV risk. Situating that argument in relation to existing work on economic organization and HIV risk as well as research on labor migration and HIV vulnerabilities, the paper demonstrates how analyzing the processes through which labor migration creates vulnerability can shift attention away from the proximate behavioral determinants of HIV risk and towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…The economic notion of externalities renders this visible(Hirsch 2014). The classic example of an externality is the pollution generated in the production of some item, the cost of which is borne by the surrounding community (either in terms of remediation or in terms of adverse health impacts)(Roberts, Mensah, and Weinstein 2010).…”
Section: Remembering Agency While Attending To Structure: the Genderementioning
confidence: 99%
See 1 more Smart Citation
“…The economic notion of externalities renders this visible(Hirsch 2014). The classic example of an externality is the pollution generated in the production of some item, the cost of which is borne by the surrounding community (either in terms of remediation or in terms of adverse health impacts)(Roberts, Mensah, and Weinstein 2010).…”
Section: Remembering Agency While Attending To Structure: the Genderementioning
confidence: 99%
“…Talking about externalities, however, says nothing about the consumer side, about demand for particular kinds of products or price elasticities. Indeed, in most work on externalities, the consuming public is configured as the object of externalities, rather than the agent of them(Hirsch 2014). A comprehensive political economic analysis should include consideration of how consumption practices shape sexuality and vulnerability to HIV.…”
Section: Remembering Agency While Attending To Structure: the Genderementioning
confidence: 99%
“…Women are known to be half of the world's migrants and also half of those living with HIV and AIDS [12,20] and labour migration and other forms of mobility have been associated with increased risk to HIV infection [55,56]. However, most of the female migrant workers are from the rural mountainous areas of Lesotho.…”
Section: Hiv/aids -Contemporary Challenges 154mentioning
confidence: 99%
“…Altman [19] and Hirsch [20] highlighted that globalisation has an impact on all aspects of life including sexuality. Sexuality is afected by globalisation in a number of interconnected ways and therefore increases inequalities, acting both as a liberator and an oppressive inluence.…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas migrants are exposed to sexual networks having different levels of HIV prevalence and different probabilities of exposure to the pandemic (Hirsch 2014; Hunter 2010). Studies have indicated that the disruption of social networks upon migration might heighten risky behaviour, owing to both diminished supervision and censure and to equally diminished social networks in their new environment, which result in isolation and loneliness (Greif & Dodoo 2011; Hunter 2010).…”
Section: Introductionmentioning
confidence: 99%